What do unions do in Mexico? - Fairris, David (Estudios Económicos de El Colegio de México, 2007)
This paper utilizes household and establishment survey data from Mexico to explore the impact of unions on wages, wage inequality, fringe benefits, turnover, job training, productivity and profits. Mexican unions are statistically significantly associated with these outcome measures for workers and firms. Unions are associated with increased wages, decreased wage inequality, increased fringe benefits per worker, increased job training and increased productivity per worker. Contrary to the broader literature on union effects, unionized establishments in Mexico experience greater worker turnover. The union association with establishment profit rates is insignificantly different from zero.